Puerarin inhibited oxidative stress and alleviated cerebral ischemia-reperfusion injury through PI3K/Akt/Nrf2 signaling pathway - Zhang, Qianqian; Yao, Min; Qi, Jiajia; Song, Rui; Wang, Lei; Li, Jiacheng; Zhou, Xian; Chang, Dennis; Huang, Qi; Li, Lili; Wang, Ning (Frontiers in Pharmacology, 2023)
Ischemic Stroke (IS) is one of the leading causes of chronic disability worldwide, oxidative stress caused by ischemia-reperfusion (I/R) injury would aggravate neuronal apoptosis or death. Studies have shown that activation of PI3K/Akt /Nrf2 pathway inhibits oxidative stress and exerts a protective effect on I/R. Puerarin (PUE) is a natural compound isolated from Puerariae Lobatae Radix, which has a neuroprotective effect on IS. However, whether the specific mechanism is related to the inhibition of oxidative stress is unclear and needs further study. To explore the therapeutic effect and underlying mechanism of PUE on cerebral I/R injury by inhibiting oxidative stress related to the PI3K/Akt/Nrf2 pathway in vitro and in vivo. The middle cerebral artery occlusion and reperfusion (MCAO/R) rats and oxygen-glucose deprivation and reperfusion (OGD/R) were selected as the in vivo and in vitro models, respectively. The therapeutic effect of PUE was observed using triphenyl tetrazolium and hematoxylin-eosin staining. Tunel-NeuN staining and Nissl staining to quantify hippocampal apoptosis. The reactive oxygen species (ROS) level was detected by flow cytometry and immunofluorescence. Biochemical method to detect oxidative stress levels. The protein expression related to PI3K/Akt/Nrf2 pathway was detected by using Western Blotting. Finally, co-immunoprecipitation was used to study the molecular interaction between Keap1 and Nrf2. In vivo and vitro studies showed that PUE improved neurological deficits in rats, as well as decreased oxidative stress. Immunofluorescence and flow cytometry indicated that the release of ROS can be inhibited by PUE. In addition, the western blotting results showed that PUE promoted the phosphorylation of PI3K and Akt, and enabled Nrf2 to enter the nucleus, which further activated the expression of downstream antioxidant enzymes such as HO-1. The combination of PUE with PI3K inhibitor LY294002 reversed these results. Finally, co-immunoprecipitation results showed that PUE promoted Nrf2-Keap1 complex dissociation.Taken together, PUE can activate Nrf2 via PI3K/Akt and promote downstream antioxidant enzyme expression, which could further ameliorate oxidative stress, against I/R-induced Neuron injury.